2014
DOI: 10.1039/c3cc47226d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for ‘carbon bonding’ in the solid state from charge density analysis

Abstract: The validity of the newly proposed 'carbon bonding', an interaction where a carbon atom acts as an electrophilic site towards a variety of nucleophiles, has been investigated in the solid state. X-ray charge density analysis provides experimental evidence for this hitherto unexplored interaction and unravels its nature and strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
153
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 23 publications
(5 reference statements)
4
153
1
1
Order By: Relevance
“…They demonstrated that the carbon atom in fact could act as an electrophilic center which can non-covalently bond with electron-rich entities leading to noncovalent carbon bonding, following a nomenclature analogous to other σ-hole interactions [7][8][9][10][11][12][13][14][15][16][17]. The theoretical predictions were confirmed experimentally by Guru Row's group [42], thus validating the existence of this type of bonding by means of X-ray charge density analysis. Electron density topologies in two prototypical crystal structures with potential carbon bonding motifs (R3N + -CH3···O/Cl) were reported and revealed two distinct features of bond paths.…”
Section: Introductionsupporting
confidence: 64%
“…They demonstrated that the carbon atom in fact could act as an electrophilic center which can non-covalently bond with electron-rich entities leading to noncovalent carbon bonding, following a nomenclature analogous to other σ-hole interactions [7][8][9][10][11][12][13][14][15][16][17]. The theoretical predictions were confirmed experimentally by Guru Row's group [42], thus validating the existence of this type of bonding by means of X-ray charge density analysis. Electron density topologies in two prototypical crystal structures with potential carbon bonding motifs (R3N + -CH3···O/Cl) were reported and revealed two distinct features of bond paths.…”
Section: Introductionsupporting
confidence: 64%
“…Its formation is attributed to a positive electrostatic potential on the group IV atomic surface [23]. On the other hand, the experimental evidence for its existence was given with charge density analysis for a large number of known crystal structures [24]. The importance of tetrel-bonding in cyclobutane rings was demonstrated by combining high level theoretical calculations and the Cambridge Structural Database (CSD) analysis, showing that tetrel-bonding interactions are quite common in nitro-substituted cubanes [25].…”
Section: Introductionmentioning
confidence: 98%
“…[30][31][32] In an sp 3 -hybridized electron-deficient C atom, there is only limited space available for an electron-rich guest molecule to nest itself. [31,32] To exem-plify this, we have represented in Figure 1 (right) the MEP sur- Figure 1.face of 1,1,2,2-tetracyanoethane (staggered conformation). The s hole is small and it is surrounded by negative belts, which hinder interactions with any concentration of negative charge (lone pair or anion).…”
mentioning
confidence: 99%
“…[6,[19][20][21][22] More recently, s-hole complexes with atoms of group IV, the tetrel (Tr) atoms, have been described, [24][25][26][27][28][29] and mostly focus on the heavier Tr atoms as tetrel-bond donors, leaving noncovalent carbon bonding much less studied. [30][31][32] In an sp 3 -hybridized electron-deficient C atom, there is only limited space available for an electron-rich guest molecule to nest itself. [31,32] To exem-plify this, we have represented in Figure 1 (right) the MEP sur- Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation